International market entry. - Lim, Ley Yen. (2008)
This Applied Research Project attempts to provide an insight on international expansion by Singapore businesses into South East Asia, specifically in the food service industry. To set the organisation for the study, a framework has been developed from the synthesis of various market entry mode and development frameworks. This research paper further attempts to give a pragmatic insight to the process of overseas expansion of a Singapore business.